Blood Adenosine Increase During Apnea in Spearfishermen Reinforces the Efficiency of the Cardiovascular Component of the Diving Reflex - Marlinge, Marion; Chefrour, Mohamed; Billaut, François; Zavarro, Marion; Rostain, Jean-Claude; Coulange, Mathieu; Guieu, Régis; Joulia, Fabrice (Frontiers in Physiology, 2021)
The physiopathology consequences of hypoxia during breath-hold diving are a matter of debate. Adenosine (AD), an ATP derivative, is suspected to be implicated in the adaptive cardiovascular response to apnea, because of its vasodilating and bradycardic properties, two clinical manifestations observed during voluntary apnea. The aim of this study was to evaluate the adenosine response to apnea-induced hypoxia in trained spearfishermen (SFM) who are used to perform repetitive dives for 4–5 h. Twelve SFM (11 men and 1 woman, mean age 41 ± 3 years, apnea experience: 18 ± 9 years) and 10 control (CTL) subjects (age 44 ± 7 years) were enrolled in the study. Subjects were asked to main a dry static apnea and stopped it when they began the struggle phase (average duration: SFM 120 ± 78 s, CTL 78 ± 12 s). Capillary blood samples were collected at baseline and immediately after the apnea and analyzed for standard parameters and adenosine blood concentration ([AD]b). Heart rate (HR), systolic (SBP), and diastolic (DBP) blood pressures were also recorded continuously during the apnea. During the apnea, an increase in SBP and DBP and a decrease in HR were observed in both SFM and CTL. At baseline, [AD]b was higher in SFM compared with CTL (1.05 ± 0.2 vs. 0.73 ± 0.11 μM, p < 0.01). [AD]b increased significantly at the end of the apnea in both groups, but the increase was significantly greater in SFM than in controls (+90.4 vs. +12%, p < 0.01). Importantly, in SFM, we also observed significant correlations between [AD]b and HR (R = −0.8, p = 0.02), SpO2 (R = −0.69, p = 0.01), SBP (R = −0.89, p = 0.02), and DBP (R = −0.68, p = 0.03). Such associations were absent in CTL. The adenosine release during apnea was associated with blood O2 saturation and cardiovascular parameters in trained divers but not in controls. These data therefore suggest that adenosine may play a major role in the adaptive cardiovascular response to apnea and could reflect the level of training.